OYSTER MUSHROOM WASTE AS MANURE IN FISH CULTURE A PRELIMINARY STUDY
In an atte1npt to recycle the waste substrates of the oyster-1nushroon1 crop, tanlis were stocked with seed of Indian n1ajor carp Cirrhinus m .. rigala at the rate of 600,000/ha and waste substrate was applied at weekly interval at 0,50,100 150;200 and 250 g/tank Oyster mushromn waste not only provided highly nutritive colonised detritus to the fish as direct feed, but also produced rich planltton in the tanl, In waste treated tanli;:s, production was better than in the control in 150, 200 and 50 g/tanl treatment suggesting the possibility of fish p oyster m.ushromn integÂ·ration. , journal=Journal of Indian Fisheries Association, author=DUBE, KIRAN and DWIVEDI, ALKESH, year=2015, month=Dec.